(untitled) (Bangladesh Journal of Agricultural Research, 2012)
A study was undertaken to examine the genetic diversity of 12 wheat (Triticum aestivum L.) genotypes, using 4 simple sequence repeats (SSRs). A total of 10 alleles were found. Allele number per locus ranged from 2 to 4 with an average of 2.5. The polymorphic information content (PIC) values ranged from 0.2755 to 0.5411 with an average of 0.3839. The average gene diversity over all SSR loci for the 12 wheat genotypes was 0.4688, ranging from 0.3299 to 0.6042. Cluster analysis based on microsatellite allelic diversity discriminated the varieties into different clusters. Genetic diversity was the highest between variety Gourab and Akbar as well as Gourab and BAW-1064, showing a genetic distance value of 0.4697. The genetic distance was lowest between Balaka and Aghrani as well as Triticale and BAW-1036. Positive correlations were found between gene diversity, number of alleles, the allele size range and the types of repeat motif of microsatellite markers. It was found from this study that microsatellite markers could characterize and discriminate all of the genotypes. More primers should be used for saturation of different regions in further studies. Bangladesh J. Agril. Res. 37(3): 389-398, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12082